Marketing of Near-border Rural Areas of Ukraine as a Factor of its Development and Stimulation of Convergence in Joint Cross-border Space with the EU (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The main problems of development of near-border rural areas of Ukraine at the present stage of European integration are outlined. In particular, the attention is focused on the lack of effectiveness of the use of resources and reducing the quality of human capital. Important problems are also labor emigration and semi-legal “shuttle trade”. These factors lead to the remaining and increasing of disparities in the economic development of rural areas on different sides of the border between Ukraine and the EU. The existence of a relationship between the level of development of border rural areas of Ukraine and the nature of convergence in total cross-border area with the EU are justified. First of all, this concerns the activation of entrepreneurship to improve the quality of life in rural cross-border territories of Ukraine. Also important are the diversification of the rural economy and stimulating the approach of its efficiency to the level of neighbouring EU-countries. Determining role of marketing for improving the management of near-border rural areas of Ukraine is revealed. At the same time, a positive influence of marketing tools for stimulating of cross-border convergence between Ukraine and the EU is demonstrated. In this sense, key aspects of marketing in near-border rural areas of Ukraine are: branding, product and pricing policy, PR and advertising, and marketing researches. Proposals to state authorities and local self-government of Ukraine are formulated. In particular, the priority directions of the using of marketing management tools for developing of near-border rural areas of Ukraine are highlighted. Special attention is paid to marketing mechanisms of intensifying the convergent processes in the transboundary space between Ukraine and the EU.
Keywords: marketing of rural areas, near-border region, cross-border cooperation, cross-border convergence, European integration